A Closed-form Solution for RSS/AoA Target Localization by Spherical Coordinates Conversion - Tomic, Slavisa (2016)
This letter addresses the problem of target localization in a 3-D space, utilizing combined measurements of received signal strength and angle of arrival (AoA). By using the spherical coordinate conversion and available AoA observations to establish new relationships between the measurements and the unknown target location, we derive a simple closed-form solution method. We then show that the proposed method has straightforward adaptation to the case where the target’s transmit power is also not known. Simulation results validate the outstanding performance of the proposed method.